A Multicenter Retrospective Study With a Minimum 5-Year Follow-up Comparing Arthroscopic Bankart Repair and the Latarjet Procedure. Issue 8 (26th August 2020) - Maman, Eran; Dolkart, Oleg; Krespi, Rafael; Kadar, Assaf; Mozes, Gabriel; Safran, Ori; Mozes, Adam; Pritsch, Moshe; Vogel, Guy; Beyth, Shaul; Chechik, Ofir; ,; et al.
Background: Arthroscopic Bankart repair (ABR) and the Latarjet procedure are surgical techniques commonly used to treat anterior shoulder instability. There is no consensus among shoulder surgeons regarding the indications for choosing one over the other. Purpose: To compare the results of the Latarjet procedure with those of ABR for the treatment of anterior shoulder instability. Study Design: Cohort study; Level of evidence, 3. Methods: Data on all patients who were treated surgically for recurrent anterior shoulder instability between 2006 and 2011 were retrospectively collected at 4 medical centers. The minimum follow-up was 5 years. Data were retrieved from medical charts, and patients were interviewed to assess their level of satisfaction (range, 0-100), functional outcomes (using the American Shoulder and Elbow Surgeons shoulder score; the Subjective Shoulder Value; and the Disabilities of the Arm, Shoulder and Hand score), and quality of life (using the 12-Item Short Form Health Survey [SF-12]). Information on return to sports activities and postoperative level of activity compared with that of the preinjury state, complications, reoperations, and recurrent instability were recorded and evaluated. Results: A total of 242 patients were included. The Latarjet procedure was performed in 27 shoulders, and ABR was performed in 215 shoulders. Patients in the ABR group had significantly higher rates of redislocation (18.5%; P = .05) and subluxation (21.4%; P = .43) but a lower rate of self-reported apprehension (43.0%; P = .05) compared with patients in the Latarjet group (3.7%, 14.8%, and 63.0%, respectively). There were 5 patients in the ABR group who underwent reoperation with the Latarjet procedure because of recurrent instability. The functional scores in the Latarjet group were better than those in the ABR group. The SF-12 physical score was significantly better in the Latarjet group than in the ABR group (98.1 vs 93.9, respectively; P = .01). Patient satisfaction and subjective scores were similar in both groups. Conclusion: These results support recently published data on the Latarjet procedure that showed its superiority over ABR in midterm stability (dislocations or subluxations). The contribution of self-reported apprehension to the broad definition of stability is not clear, and apprehension rates were not correlated with satisfaction scores or the recurrence of dislocation or subluxation.